Dietary oleic acid contributes to the regulation of food intake through the synthesis of intestinal oleoylethanolamide - Igarashi, Miki; Iwasa, Kensuke; Hayakawa, Tetsuhiko; Tsuduki, Tsuyoshi; Kimura, Ikuo; Maruyama, Kei; Yoshikawa, Keisuke (Frontiers in Endocrinology, 2023)
Among the fatty acid ethanolamides (FAEs), oleoylethanolamide (OEA), linoleoylethanolamide (LEA), and palmitoylethanolamide (PEA) are reported to be involved in feeding regulation. In particular, OEA is well characterized as a satiety signal. Following food consumption, OEA is synthesized from oleic acid (OA) via an N-acyl phosphatidylethanolamine-specific phospholipase D-dependent pathway in the gastroenterocytes, and OEA induces satiety by recruiting sensory fibers. Thus, we hypothesized that dietary OA is an important satiety-inducing molecule. However, there has been no direct demonstration of the effect of dietary OA on satiety induction without the influence of the endogenous biosynthesis of OA from stearic acid (SA) or other FAEs. In this study, we used two experimental diets to test our hypothesis: (i) an OA diet (OAD; 38.4 mg of OA/g and 7.2 mg of SA/g) and (ii) a low OA diet (LOAD; 3.1 mg of OA/g and 42.4 mg of SA/g). Relative to mice fed the OAD, mice fed the LOAD for two weeks exhibited reduced levels of jejunal OEA but not jejunal LEA and PEA. The LOAD-fed mice showed an increase in food intake and body weight gain. Moreover, LOAD-induced increase in food intake was immediately observed after the switch from the OAD, whereas these effects were diminished by the switch back to the OAD. Furthermore, treatment with OA and OEA diminished the effects of LOAD on food intake. Collectively, these results show that dietary OA is a key factor in the reduction of food intake and increase in satiety mediated by OEA signaling.